Trajectories of post-traumatic stress in sepsis survivors two years after ICU discharge: a secondary analysis of a randomized controlled trial - Schmidt, Konrad; Gensichen, Jochen; Schroevers, Maya; Kaufmann, Martina; Müller, Friederike; Schelling, Gustav; Gehrke-Beck, Sabine; Böde, Monique; Heintze, Christoph; Wensing, Michel; Schwarzkopf, Daniel (Critical care, 2024)
Post-traumatic stress has been identified as a frequent long-term complication in survivors of critical illnesses after sepsis. Little is known about long-term trajectories of post-traumatic stress and potentially modifiable risk factors following the ICU stay. Study objective was to explore and compare different clinical trajectories of post-traumatic stress symptoms in sepsis survivors up to two years after discharge from ICU.